(untitled) (Carte Romanze. Rivista di Filologia e Linguistica Romanze dalle Origini al Rinascimento, 2015)
The Proemium in Historia Apollonii is a short introduction to the Historia Apollonii regis Tyri extant in two manuscripts from fourteenth-century Italy. It constitutes an unusual instance of medieval theorizing about the narrative structure of the genre of ancient romance. In this article I present the text of the Proemium, evaluate the evidence it provides about the circulation and reception of the Historia Apollonii, and raise the possibility that this text might lie behind Boccaccio’s description of the narrative structure of the stories recounted in Day Two of the Decameron. Il Proemium in Historia Apollonii è una breve introduzione all’Historia Apollonii regis Tyri conservata in due manoscritti copiati in Italia nel Trecento, la quale costituisce un raro esempio di teorizzazione medievale della struttura narrativa del genere del romanzo antico. In quest’articolo presento un’edizione del Proemium, valutando le prove che offre rispetto alla circolazione e ricezione dell’Historia Apollonii, e formulando l’ipotesi che questo testo possa aver condizionato la descrizione offerta da Boccaccio della struttura narrativa delle novelle della seconda giornata del Decameron.